Efektivitas Gen CP PSTV dalam Memproteksi Nicotiana benthamiana Transgenik TO terhadap Serangan Peanut Stripe Virus - Sholeh Avivi; Sudarsono Sudarsono; Satriyas Ilyas; Hajrial Aswidinnoor (Jurnal Perlindungan Tanaman Indonesia, 2005)
The aims of this research were: (1) to obtain the transgenic Nicotiana benthamiana T0 which have various cp Peanut stripe virus (PStV) genes construct (pBINRCP 1, pBINRCP2, pBINRCP3, and pBINRCP4); (2) to investigate the resistance of transgenic N. benthamianaT0 toward PStV infection; (3) to investigate the effectiveness of those construct to protect N. benthamiana T0 toward PStV infection. To achieve those objectives N. benthamiana T0 (70 plants) were regenerated, PCR tested and infected with PStV using biological analysis methods. The result showed that all of PStV construct gave the resistancy toward PStV infection. The phenotypic respon of those plants were the PBINRCPl plants 35.7% resistance, 0% recovery, and 64.3% susceptible, the PBINRCP2 plants 41.7%, resistance, 0% recovery, and 58,3% susceptible, the PBINRCP3 plants 71.4% resistance, 0% recovery, and 28.6% susceptible, and the PBINRCP4 plants 25.0% resistance, 25.0% recovery, and 50.0% susceptible.